DINAMIKA GERAKAN MUHAMMADIYAH DI ERA SEBELUM KEMERDEKAAN DALAM MERINTIS GERAKAN TAJDID KEUMATAN - Dartim Dartim (Universitas Muhammadiyah Surakarta, 2021)
This article discusses the dynamics of the Muhammadiyah Movement as a tajdid movement during its journey in the pre-independence era and ahead of independence. Various socio-political phenomena of the people occurred at that time. The writing approach is carried out with a scientific framework with various related document sources. After conducting a comprehensive search and analysis, it was found that Muhammadiyah as a renewal organization was initiated by the reality of indigenous people who experienced oppression in the form of impoverishment, ignorance and restrictions on religious space. The renewal of Muhammadiyah in the pre-independence period was carried out by means of renewing religious understanding and renewing attitudes in understanding religion itself. Muhammadiyah real action through the world of education, social, health and national politics.